NURSING CONSULTATION IN BASIC CARE: DIFFICULTIES AND CHALLENGES (Fiep Bulletin - online, 2019)
This paper presents an exploratory field research, with a qualitative approach, with the content analysis according tothe methodological framework proposed by Bardin. The overall purpose was to know the experience of the nurse professionalregarding the nursing consultation in Basic Care. The data collection was conducted through a questionnaire containing 05 (five)subjective questions which were asked to 30 (thirty) nurses that operate Basic Care in Cascavel - Western Paraná during August,2016. Professionals were randomly selected. Data collection and results analysis were grouped into 02 (two) categories: I. Thetechnical-scientific knowledge applied in the nurses' practice in nursing consultation, composed of 1 (one) subcategory: II. Theimportance of the nursing consultation in the perception of the nurses and the Category II. The practice of nurses facing theapplication of nursing consultation consists of two (2) subcategories: II. The difficulties and challenges experienced by nurses inthe nursing consultation. II.II The experience of nurses facing the nursing consultation. It is concluded that nurses consider thenursing consultation in Basic Health Care a tool of fundamental importance, contributing to solve the health problems of thepopulation, as well as an improvement in quality of live of those who benefit from health services. However, there are challengesto overcome.
Keywords: Nursing Consultation; Basic Care; Professional practice